Liquid Chromatography/Mass Spectroscopy and TLC Analysis for the Identification of Sugars Extracted from the Outer Skin of Almond Fruit (Prunus dulcis) - Chidan Kumar2‡, S. Chandraju1*, R. Mythily1 and C. S. (Recent Research in Science and Technology, 2011)
A rapid, sensitive extraction method was developed using the mixture Methanol - Dichloromethane - Water (MDW) (0.3:4:1v/v/v) and MeOH-H2O phase was assayed for sugar analysis. Photodiode-array detection (DAD) has been used to prove the extracted compound is UV inactive, High-performance liquid chromatography (HPLC) with Evaporative Light Scattering Detector (ELSD) coupled to electrospray ionization mass spectrometric (ESI-MS) detection in the positive ion mode gave MS and MSn fragmentation data which were employed for their structural characterization. The various standard sugars were spotted using the solvent system n-butanol - acetone - diethylamine – water (10:10:2:6, v/v/v/v) in the cellulose layer for TLC analysis which indicated the presence of lactose, sucrose, galactose, xylose. This is the first assay of the sugar profile of the almond fruit outer skin, which can be further developed for characterization and evaluation of their quality with regards to their sugar composition.